Pertumbuhan Tanaman Lada (Pipper nigrum L.) Umur Satu Tahun pada Lahan Bekas Tambang dengan Penambahan Dosis Pupuk Hayati yang Berbeda - Badriyah Badriyah; Ismed Inonu; Euis Asriani (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Badriah B, Inonu I, Asriani E. 2019. Growth of one year old pepper (Pipper nigrum L.) in post tin mining land using different dosage biofertilizer. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands. 8(2):117-125.Â Â Â The yield of pepper as important spice plant has been decreased due to the reduction of pepper planting area which are converted into tin mining area. One effort can be done is utilizing suboptimal lands that has low soil fertility. The aim of this research was to determine the effect of biofertilizer dosage on one year old pepper to growth in post tin mining land. This research had been conducted from February 2018 until June 2018 in post tin mining land owned by PT Timah at Dwi Makmur Village, Bangka. The research used expremental method with Completely Randomized Block Design (CRBD) with single factor. The factor was biofertilizer dosage: (0,0; 0,5; 1,0; 5,0; 10,0; and 15,0 g/L/plant). The result showed enrichment biofertilizer significantly effect on chlorophyll content and number of branch, but not significantly on plants height, number of nodes, and leaf area. The treatment dosage 10 g/L/plant (1x108 cfu) was the best inclined result growth of one year old pepper plant in post tin mining land.